Cover Picture: Eur. J. Immunol. 3'14. (March 2014) - Unknown
<x xml:space="preserve">Abstract</x> The cover features a kidney section from a CD19Cre mouse, which was sampled four days after induction of nephrotoxic nephritis and stained with sheep IgG. The image is taken from the article by Kluger et al. (pp. 683–693) in which the authors show that B‐cell‐derived IL‐10 does not play a role in the clinical course of glomerulonephritis. The authors show that cytokine production, leukocyte composition, proliferation, and activation are indistinguishable between wild‐type mice and mice lacking B‐cell‐derived IL‐10, while production and renal deposition of Ag‐specific IgG are mildly impaired in the absence of B‐cell‐produced IL‐10. These data suggest that although IL‐10‐secreting B cells may have protective effects, a relevant anti‐inflammatory role for B‐cell‐derived IL‐10 requires further study in other models of inflammatory disease.